WAYS OF USING INFORMATION TECHNOLOGIES IN IMPROVING STUDENTS' COMMUNICATIVE COMPETENCE IN ENGLISH CLASSES (International Conference on Modern Science and Scientific Studies, 2025)
Currently, the role of information technologies in the educational process is increasing. These technologies are especially important in improving communicative competence in English classes. Information technologies provide an opportunity to make the language learning process of students more interesting, effective and interactive. This article provides information on how information technology can be used to improve communicative competence in English classes.